Remote active control of nanoengineered materials for dynamic nanobiomedical engineering. Issue 4 (16th October 2020) - Kim, Yuri; Choi, Hyojun; Shin, Jeong Eun; Bae, Gunhyu; Thangam, Ramar; Kang, Heemin
Abstract: Cells dynamically interact with native nanostructured extracellular matrix at a molecular level in vivo. Developing remotely and actively controllable nanoengineered biomaterials can manipulate and unravel complex cell‐material interactions that dynamically occur in the nanoscale in vivo. In this review, we discuss emerging advances in a myriad of recent nanoengineering technologies to design remotely manipulable materials that enable dynamic nanobiomedical engineering at the molecular level. In particular, we focus on remote active stimuli, such as magnetic fields, light, in situ self‐assembly, and ultrasound, to manipulate dynamic cell‐material interactions in both in vitro and in vivo settings. Remote active control can be particularly appealing with targeting capability for particular locations at any prescribed time points with a degree of reversibility. The unique remote controllability enables the regulation of cellular signaling, adhesion, differentiation, and polarization; cell, drug, and gene delivery; and in situ self‐assembly. These materials allow the remote control in regenerative medicine, immunotherapy, cancer therapy, and biocatalysis as well as mechanistic studies on dynamic nanoscale cell‐material interactions. We also highlight current challenges in the remote active control, such as reproducibility, tissue‐penetrative capability, noninvasive surgery, spatial localization, and temporal variation. Albeit remotely and actively controllable nanoengineered biomaterials are in the nascent stage of development, they can evolve into multiresponsive, reversible, and cost‐effective three‐dimensional systems with safe and convenient long‐term control at the cell, tissue, and organ level toward clinical patient‐tailorable on‐demand therapy. Abstract : Developing remotely and actively controllable nanoengineered biomaterials can manipulate and unravel dynamic cell‐material interactions at the molecular level. In this review, the authors discuss the use of remote active stimuli, such as magnetic fields, light, in situ self‐assembly, and ultrasound, for dynamic nanobiomedical engineering of regenerative medicine, immunotherapy, cancer therapy, biocatalysis, and cell/drug delivery. Remotely and actively controllable nanoengineered biomaterials can realize safe, convenient, noninvasive, location‐ and time‐regulatable patient‐tailorable on‐demand therapy.